Management of Neglected Achilles Tendon Division: Assessment of Two Novel and Innovative Techniques. (11th February 2014) - Jain, Pradeep; Dutta, Parthapratim; Goswami, Prabal; Patel, Amol; Purwar, Shammi; Jain, Vaibhav
Abstract : Objective . Repair of injured Achilles tendon in neglected cases is one of the difficult and challenging procedures for surgeon. Here, we share our experience with the use of two innovative techniques for repair of chronic rupture of Achilles tendon. Design . Prospective Study. Setting . Tertiary care hospital. Patients . Twelve patients with chronic Tendo Achilles rupture were followed up over a period of three to five years. Intervention . Patients were divided in two groups, A and B. In Group A, the repair was done with Gastroc-soleus turndown flap and weaving with Plantaris tendon graft and in Group B, with modified Kessler's technique strengthened with the free plantaris tendon graft. Outcome Assessment . Clinically and by Modified Rupp Scoring system. Results . At an average follow-up of 4 years (Group A, 3.7 and Group B, 4.4 years), the majority of the patients had excellent to good results as assessed with Modified Rupp Scoring with few minor complications in both the groups. There was no significant difference in the baseline variables such as age and gender and also in the Rupp's score between the two groups. Conclusion . The two techniques are novel and simple and have been found to be useful for repair of chronically ruptured Achilles tendon.